Immediate changes in stroke patients’ gait following the application of lower extremity elastic strap binding technique - Liu, Yuduo; Wang, Qi; Li, Qiujie; Cui, Xueji; Chen, Huimeng; Wan, Xianglin (Frontiers in Physiology, 2024)
Objective To ascertain the immediate changes in stroke patients’ temporal and spatial parameters of gait and the joint angles of stroke patients throughout the entire gait cycle following the application of lower extremity elastic strap binding technique. Methods Twenty-nine stroke patients were invited as the study participants. The patient seated, flexed the hip and knee, utilized a 5cm-wide elastic strap, positioning its midpoint beneath the affected foot and crossing it anterior to the ankle joint. Upon standing, the strap encircled the posterior aspect of the lower leg, proceeded around the back of the knee, and ascended the thigh on the affected side. Crossing anteriorly over the thigh, it then encircled the back of the waist before being secured in place. Using Qualisys motion capture system to collect kinematic data of the lower extremities during walking while wearing shoes only or strapping. A paired sample t-test was used to analyze the effects of the technique on gait spatiotemporal parameters and joint angles in stroke patients. Results The patients’ step length decreased (P=0.024), and step width increased (P=0.008) during the gait cycle after the strapping. In the gait cycle between 0% to 2%, 7% to 77%, and 95% to 100%, the hip flexion angle on the affected side was significantly larger after the strapping (P<0.05). In the gait cycle between 0% to 69% and 94% to 100%, the knee flexion angle on the affected side was significantly larger after the strapping (P<0.05). In the gait cycle between 0% to 57% and 67% to 100%, the ankle dorsiflexion angle on the affected side was significantly smaller after the strapping (P<0.05), and in the gait cycle between 0% to 35% and 68% to 100%, the ankle inversion angle on the affected side was significantly smaller after the strapping (P<0.05). Conclusion The lower extremity elastic strap binding technique can decrease the hip flexion and knee flexion limitations in stroke patients during walking, and reduce the ankle plantar flexion and ankle inversion angle of stroke patients. The lower extremity elastic strap binding technique enabled stroke patients to adopt a more stable gait pattern.